Reforming the Malaysian tax system: the effects of Special Voluntary Disclosure Programme (SVDP), role of Inland Revenue Board Malaysia (IRBM), and demographics of taxpayers on Malaysian tax awareness - Nadiah Abd Hamid,; Soliha Sanusi,; Mira Atilia Noor Adzlan,; Nur Munirah Roslan,; Amirul Azri Ayob, (Penerbit Universiti Kebangsaan Malaysia, 2022)
A sound tax system improves government revenue by encouraging voluntary tax compliance to ensure good tax awareness among citizens. However, many issues arise with regard to tax collection. As these issues remain unresolved, the government needs to frequently implement a tax amnesty programme which is not sustainable or cost-effective in the longer run. Tax awareness becomes a significant factor in managing tax compliance behaviour within contemporary literature. Hence, this paper aims at ascertaining the effects of Special Voluntary Disclosure Programme (SVDP), the role of Inland Revenue Board Malaysia (IRBM), and demographic factors on tax awareness among Malaysian taxpayers. This paper used Smart PLS version 3 to run the data. The results confirmed that SVDP, IRBM’s role, and public/ private sectors’ employment are crucial in influencing tax awareness. These findings have implications for tax policies, such as developing tax knowledge programmes and raising public awareness among individual taxpayers in Malaysia.